High-Speed and Continuous-Wave Programmable Luminescent Tags Based on Exclusive Room Temperature Phosphorescence (RTP) - Gmelch, Max; Achenbach, Tim; Tomkeviciene, Ausra; Reineke, Sebastian (Advanced Science, 2021)
Most materials recently developed for room temperature phosphorescence (RTP) lack in practical relevance due to their inconvenient crystalline morphology. Using amorphous material systems instead, programmable luminescent tags (PLTs) based on organic biluminescent emitter molecules with easy processing and smooth sample shapes are presented recently. Here, the effective quenching of the emitter's RTP by molecular oxygen (O-2) and the consumption of the excited singlet O-2 through a chemical reaction represent the central features. With customized activation schemes, high-resolution content can be written and later erased multiple times into such films, providing a versatile yet simple photonic platform for information storage. However, two important limitations remain: The immutable fluorescence of the emitters outshines the phosphorescent patterns by roughly one order of magnitude, allowing readout of the PLTs only after the excitation source is turned off. The programming of these systems is a rather slow process, where lowest reported activation times are still >8 s. Here, a material-focused approach to PLTs with fast activation times of 120 +/- 20 ms and high-contrast under continuous-wave illumination is demonstrated, leading to accelerated programming on industry relevant time scales and a simplified readout process both by eye and low cost cameras.
Keywords: photo-induced optical memory; programmable tags; room temperature phosphorescence; RTP; smart materials